Pedagogical Support in Human Talent Management: A Systematic Review - Roña Córdova, Milquiades Enrique (2024)
This systematic review explored the impact of pedagogical coaching on human talent management and teacher perf ormance over the past f our years. A qualitative approach was employed using the PRISMA methodology to conduct searches in the f ollowing databases:Scopus, SciELO, Redalyc, Dialnet, Erih Plus, Latindex, the University of César Vallejo library, and other relevant databases.Inclusion and exclusion criteria were applied. For inclusion, articles published between 2021 and 2024 that addressed pedagogicalcoaching in the context of human talent management and teacher perf ormance were considered, while studies that did not f ocus on educational contexts, were not peer-reviewed, or were not available in f ull text were excluded. Through the analysis of 229 studies, it was f ound that pedagogical coaching has a positive ef f ect on improving teaching practices and teacher satisf action. However, the ef f ectiveness of coaching varies depending on the context and the quality of its implementation. The results suggest the need to strengthen the training of coaches, personalize support, and establish clear regulatory f rameworks to ensure the quality of coaching. This review contributes to consolidating pedagogical coaching as a key strategy to improve educational quality and teacher prof essional development.